PELATIHAN PEMBUATAN LIGHT TRAP DAN INSECTISIDA ORGANIK SEBAGAI PENGENDALI HAMA PENGGEREK BATANG PADI BAGI KELOMPOK TANI DI DESA BLANG BATEE - Fitriani Fitriani; T. Andi Fadhly; Fadhliani Fadhliani; Yulina Ismida (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Recently rice productivity has decreased due to the attack of stem borer pests that have been resistant to the use of an insecticide. Also, the adoption technology level of farmers is still limited and tends to slow down, which can see from the symptoms of stagnation in rice productivity and community welfare. Therefore, increasing farmers' knowledge in optimizing the use of local resources in improving national food security must be improved. One of them is by empowering farmer groups in the manufacture of light traps and organic insecticides as a monitoring tool and controlling fluctuations in stem borer pest population. That rice productivity can increase, increasing the role and function of extension workers, university (PT) and farmer groups in accelerating and expanding innovation adoption agriculture to support agricultural development through partnerships, government, and institutions. The method used is the direct method approach, including a location survey, socialization, lecture, and practice. The results have shown knowledge and skill increase of public about the implementation of light trap and organic insecticides that are equal to 90% and 95%. These data show that the application of light traps and natural pesticides has a positive impact on the community so that it expects that the implementation of the program can produce products that can reduce the population of stem borer pests to increase rice productivity.